Brazilian version of Paykel interview for recent life events (Brazilian Journal of Behavioral and Cognitive Therapy, 2002)
In the current time, one of the most used instruments in life events studies is the Interview for recent life events developed by Eugene Paykel(UK). It is a semi-structured interview with 64 specific variables divided in ten life events categories: work, education, finances, health, bereavement, migration, courting and cohabitation, legal, family and social relationship. The Paykel interview was translated to French, Italian, Germany, Bengali, Kannada (an Indian dialect) and Arabian. The present study goal is to make this instrument available for research in Portuguese language countries, by a process of validated translation. The Paykel interview was translated to Portuguese by a professional translator and by a bilingual Brazilian psychiatrist. Afterwards, the Portuguese version was back-translated to English by a bilingual English psychiatrist and, then, sent to Professor Paykel, who approved the final version.